The Relationship of Hemoglobin Levels and Compliance with Drinking Zinc with Recurrent Diarrhea in Toddler - Nurjannah Supardi; Rahayu Rahayu; Nahira Nahira; Tamzil Azizi Musdar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Diarrhea can be defined as a condition in which a person defecates with more liquid feces than usual and with a frequency of three or more times in 24 hours. Diarrhea is closely related to the occurrence of stunting cases. Diarrhea generally attacks toddlers because their immune systems are still weak and vulnerable. WHO and UNICEF policies in the treatment of diarrhea are the provision of oralit and zinc, based on research over 20 years. Iron plays a role in various physiological processes of the body, one of which is the immune system. The purpose of the study was to determine the relationship between hemoglobin levels and compliance with zinc intake with the incidence of recurrent diarrhea in toddlers at the Jaury Jusuf Putera Makassar Academic Hospital. The research design used was a non-experimental analytical cross-sectional study, namely a study conducted observationally to see the relationship between hemoglobin levels and compliance with zinc intake with the incidence of recurrent diarrhea, without providing treatment to the research subjects. The sample in the study was toddlers who experienced recurrent diarrhea at the Jaury Jusuf Putera Makassar Academic Hospital in March - May 2024 as many as 32 people. The results of the study showed that there was a relationship between hemoglobin levels and the incidence of recurrent diarrhea (p = 0.015). And there was a relationship between compliance with zinc consumption and the incidence of recurrent diarrhea (p = 0.004). It is recommended that health workers provide more education and control over the use of zinc drugs given in the management of diarrhea, as well as educate to maintain normal hemoglobin levels in toddlers. So that it can reduce the prevalence of recurrent diarrhea.